Exploring Business (Open textbook library., 2016)
The author's goals in writing Exploring Business Version 2.0 was simple: introduce students to business in an exciting way. Exploring Business is adapted from a work produced by a publisher who has requested that they and the original author not receive attribution. This adapted edition is produced by the University of Minnesota Libraries Publishing through the eLearning Support Initiative. Though the publisher has requested that they and the original author not receive attribution, this adapted edition reproduces all original text and sections of the book, except for publisher and author name attribution. This textbook has been used in classes at: College of Alameda, Columbia Basin College, Flagler College, Johnson County Community College, Pasadena City College, Penn State University, Renton Technical College, San Diego Mesa College, Sierra College, Yuba College.